A Bizarre Presentation of Vulvar Nevus Lipomatosis Superficialis - Priyadarshan Anand Jategaonkar; Sudeep Pradeep Yadav; Gayatri Khatri Yadav; Smita Priyadarshan Jategaonkar (Journal of Clinical and Diagnostic Research, 2024)
A 24-year-old girl presented to the Outpatient Department with multiple painless, insidious-onset swellings on the pubic area. Initially, they started as pin-head nodules when she was just eight years old and gradually increased in number and size. Apart from occasional itching in the area, she never experienced any noticeable symptoms over the years. However, as she grew older, concerns about cosmetic issues at marriage age compelled her to seek medical advice. Her past and family histories were not contributory. She had no addictions, medical co-morbidities, or local trauma.